Gradišče on Sloka gora and Vinji hrib above Vino on the north-western edge of the Dolenjska Hallstatt community - Tecco Hvala Sneža (Arheološki vestnik, 2021)
Test excavations on Sloka gora and Vinji hrib above Vino, carried out in 1999 as part of the research of prehistoric fortified settlements in the Dolenjska region, illuminate the north-western edge of the settlement of the Dolenjska Hall- statt community. These are smaller hilltop settlements in the hilly hinterland of Ljubljana, in which two phases have been identified, probably of the Late Hallstatt period according to otherwise modest finds.